The imaginary Synagogue : anti-Jewish literature in the Portuguese early modern world (16th-18th centuries) - Feitler, Bruno (Medieval and early modern Iberian world, 2015)
This book scrutinizes literary works based on Judaism, Jews and their descendants, written or printed by the Portuguese between the forced conversion of Jews in 1497 and the ending of the distinction between New and Old Christians in 1773. It tries to understand what motivated this vast literary production, its different currents, and how they evolved. Additionally, it studies the image of New Christians and seeks the reasons for the perpetuation of this perception of Jewish descendants in the Early Modern Portuguese world. This book seeks to identify which Jews and which synagogue those authors constructed in their texts and their reasons for doing so, and offers conclusions on the self-affirmed Catholic importance of this literary current.